Assessment of operative competency for thyroidectomy: Comparison of resident self‐assessment vs attending surgeon assessment. Issue 12 (19th August 2020) - Kim, Alexandrea H.; Vaughn, Cory A.; King, Deanne L.; Maizels, Max; Meade, Patrick; Stack, Brendan C.
Abstract: Background: Self‐awareness of skill, essential for progression as a surgeon, has direct bearing on postresidency practice; however, studies have supported that residents achieve self‐perceived competence later than believed by program directors. This study compares residents' self‐perception of operative competency to attending surgeon's evaluation using Computer Enhanced Visual Learning, a validated online hemithyroidectomy‐specific assessment tool. Methods: Eleven otolaryngology‐Head and Neck Surgery (HNS) residents completed a preoperative module and postoperative survey, later reviewed by an attending surgeon. Eighty‐three performances were assessed for inter‐rater reliabilities of key surgical steps. Results: Almost perfect agreement (Kappa = 0.81‐1.00) was shown in 11 of 18 parameters. Substantial agreement (Kappa = 0.61‐0.80) was demonstrated in the remaining seven parameters. Conclusions: Otolaryngology‐HNS trainees have high self‐awareness of their performance at each step in a hemithyroidectomy. Standardized assessment tools can allow for documentation of procedural performance and serve as guides for improvement. This is the only study to examine otolaryngology‐HNS trainees' self‐perceived skill compared to an attending surgeon's assessment for hemithyroidectomy.